Dynamic tuneable G protein-coupled receptor monomer-dimer populations - Patricia M. Dijkman (Nature Portfolio, 2018)
Evidence suggests oligomerisation of G protein-coupled receptors in membranes, but this is controversial. Here, authors use single-molecule and ensemble FRET, and spectroscopy to show that the neurotensin receptor 1 forms multiple dimer conformations that interconvert - “rolling” interfaces.